The History of the Transport System Development and Future with Sharing and Autonomous Systems - Geza Katona; Janos Juhasz (Communications - Scientific letters of the University of Zilina, 2020)
The world today is rapidly changing with the spread of automation. Moreover, urban life is more and more common and the number of inhabitants is rapidly growing. This time is the renaissance of bicycle-based vehicles, especially of electric power assisted bicycles. Vehicle sharing is also getting more popular. These progresses will have a crucial effect on traditional transportation networks. Moreover, the traffic volume, parking facilities and public space usage can be drastically modified. A research data is introduced from Paris and Lisbon, which helps to forecast the effect of the autonomous and sharing systems. This evolution can be advantageous, but it can also bring some disadvantages. In this article, these changes are summarized in the mirror of history, especially the Futurama concept and the transport system changes in Los Angeles. This overview will be a good basis for further research and for the development of a routing algorithm.